Recent Advances of MOFs and MOF‐Derived Materials in Thermally Driven Organic Transformations. Issue 9 (29th November 2018) - Yang, Shuliang; Peng, Li; Bulut, Safak; Queen, Wendy L.
Abstract: Owing to the almost boundless structural tunability, MOF and MOF‐derived catalysts have recently exhibited structures of higher complexity, and hence, have demonstrated activity in a wide array of organic transformations. These reactions have a broad range of important applications ranging from pharmaceuticals to agriculture. Given the increasing number of publications in the area, this Minireview is focused on the most recent advancements in thermally driven organic transformations using both MOFs, nanoparticle@MOF (NP@MOF) composites, and several classes of MOF‐derived materials. The most recent advancements made in materials design and the utility of these materials in a broad range of reactions are discussed. Abstract : Lookin′ for some hot stuff : This Minireview describes the most recent advancements in thermally driven organic transformations using MOFs, nanoparticle@MOF composites, and several classes of MOF‐derived materials.